Mozambique : Assessment of the Public Procurement System - World Bank Group (World Bank, Washington, DC, 2021)
The Mozambique country procurement assessment based on the methodology for assessing procurement systems (MAPS II) methodology was carried out from September 2018 to June 2019, at the initiative of the Government of Mozambique (GOM) through the functional unit for supervision of procurement (UFSA). MAPS II methodology, 2018 is a universal tool reflective of leading international procurement practice that serves as a guide towards sustainable and inclusive public procurement (PP) reform. Mozambique government decided to benefit from MAPS II upgraded analytical framework in order to get more visibility into the PP existing challenges and opportunities that lie ahead. Based on these findings, a comprehensive and inclusive strategic plan was formulated to guide the way forward, towards improved procurement outcomes. The assessment of the Mozambique PP systems against the criteria set out in the MAPS II methodology, confirmed the progress achieved in the establishment of the legal and institutional framework for PP. The focus of this report is the core government procurement under the Regulamento, while briefly addressing PP under the state owned enterprises (SOE) and public private partnership (PPP) laws.